2022
DOI: 10.1186/s12951-022-01516-4
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-21 regulating PVT1/PTEN/IL-17 axis towards the treatment of infectious diabetic wound healing by modified GO-derived biomaterial in mouse models

Abstract: Background Diabetic foot ulcer (DFU), persistent hyperglycemia and inflammation, together with impaired nutrient and oxygen deficiency, can present abnormal angiogenesis following tissue injury such that these tissues fail to heal properly. It is critical to design a new treatment method for DFU patients with a distinct biomechanism that is more effective than current treatment regimens. Method Graphene oxide (GO) was combined with a biocompatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Both miR-21 and miR-210 are known to be activated by hypoxic conditions. Hypoxia occurs in cancer, during wound healing, as well as in other pathological conditions [ 24 , 25 , 26 , 27 , 28 ]. Lowering miR-21 and miR-210 expression decreases cell migration and invasion of pancreatic stellate cells (PSCs) and CAFs [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both miR-21 and miR-210 are known to be activated by hypoxic conditions. Hypoxia occurs in cancer, during wound healing, as well as in other pathological conditions [ 24 , 25 , 26 , 27 , 28 ]. Lowering miR-21 and miR-210 expression decreases cell migration and invasion of pancreatic stellate cells (PSCs) and CAFs [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that the improved GO-based wound dressing has the potential to increase the production of sEVs by increasing the amount of miR-21 that is produced by AD-MSCs [ 92 ]. In order to enhance wound healing in the diabetic foot (DF), it has been discovered through bioinformatics research and testing that PVT1 is the most important long noncoding RNA (lncRNA).…”
Section: Targeting Il-17 Pathways For Enhanced Healing In Chronic Wou...mentioning
confidence: 99%
“…This loading model can stimulate cells to secrete cytokines and thus promote cell proliferation and remodeling. Chen et al 71 designed a hydrogel loaded with graphene oxide (GO). This hydrogel loaded with GO can induce sEVs secretion of miR‐21‐5p in adipose‐derived MSCs through up‐regulating the phosphoinositide‐3 kinase (PI3K)/protein kinase B (PKB/AKT) signal pathway.…”
Section: Classification and Biological Functions Of Hydrogelsmentioning
confidence: 99%